2007
DOI: 10.1021/pr0700753
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profiling of Plasma in Huntington's Disease Reveals Neuroinflammatory Activation and Biomarker Candidates

Abstract: Huntington's disease (HD) causes widespread CNS changes and systemic abnormalities including endocrine and immune dysfunction. HD biomarkers are needed to power clinical trials of potential treatments. We used multiplatform proteomic profiling to reveal plasma changes with HD progression. Proteins of interest were evaluated using immunoblotting and ELISA in plasma from 2 populations, CSF and R6/2 mice. The identified proteins demonstrate neuroinflammation in HD and warrant further investigation as possible bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
149
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 203 publications
(170 citation statements)
references
References 33 publications
12
149
2
2
Order By: Relevance
“…Blood samples were obtained from control subjects and patients with genetically diagnosed HD and processed as described previously (10). The patients were clinically assessed by a neurologist experienced in assessment of HD patients.…”
Section: Isolation Of Human Blood Monocytes and Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood samples were obtained from control subjects and patients with genetically diagnosed HD and processed as described previously (10). The patients were clinically assessed by a neurologist experienced in assessment of HD patients.…”
Section: Isolation Of Human Blood Monocytes and Macrophagesmentioning
confidence: 99%
“…Levels of soluble immune markers in serum, such as soluble TNF receptor, IL-2 receptor, and immunoglobulins, are elevated in HD patients (9,10). Plasma samples from HD patients also have increased levels of proinflammatory cytokines and chemokines that correlate with disease progression (11,12), occurring years before the onset of chorea and other HD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other neurodegenerative diseases, there is an increase in clusterin levels as well as cytokines IL-6 and IL-8 reported in HD [57]. A small sample proteomic study detected significantly higher levels of prothrombin and haptoglobin which both are proteins associated with inflammatory response [61].…”
Section: Inflammatory Markersmentioning
confidence: 59%
“…Overactivation of myeloid cells, including microglia, and subtle abnormalities of the innate immune system, are among the earliest biochemical changes that have so far been detected in HD patients [15,57]. Most of this work has been carried out in peripheral blood or ex vivo cells [58] but in 2007 Dalrymple and colleagues found that plasma elevations of clusterin were mirrored in CSF from 20 patients and 10 controls in the first report from a CSF collection with dedicated matched contemporaneous healthy controls from the general population, rather than from patients under investigation for other conditions [12].…”
Section: Inflammatory Markersmentioning
confidence: 99%
“…Newly identified biomarker candidates that require further investigation include cholesterol metabolites [14] and indirect markers of transcriptional dysregulation such as the histone component H2AFY [15]. Meanwhile clusterin, which our own work revealed as a possible HD plasma biomarker [16], has since been highlighted as a major genetic modifier and possible blood biomarker of Alzheimer's disease [17].…”
Section: Biofluidsmentioning
confidence: 91%